Reparations for Child Victims of Armed Conflict: Responding to the Rights and Needs of Children in Transitional Justice - Miano, Sarah M. (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Modern warfare disproportionately affects children caught in the midst of complex and persistent conflict. Harm against young people, however, is not merely an unfortunate byproduct of war. Rather, children are frequently targeted in serious crimes under human rights and humanitarian law, including killing, sexual violence, recruitment and use in armed forces or groups, maiming, torture, and denial of basic services, to name a few. Unfortunately, children's roles as political, economic, and social actors are often undervalued, and their experiences during war are consequently deprioritized on post-conflict agendas. Yet, children are rights-holders and agents of social transformation, and processes seeking justice for victims of armed conflict are remiss to ignore this significant group. This paper explores the potentially meaningful role reparations processes and outcomes can play in facilitating justice for children victimized through serious crimes during armed conflict. Part 1 reviews the transitional justice framework, focusing on existing legal and normative guidance on reparations. This section also introduces children's rights principles, including non-discrimination, best interests, and evolving capacities of the child, which are applied throughout the analysis to ensure children's needs, rights, and protection are prioritized. Part 2 looks at children's experiences of war and the long-term and immediate impact of crimes on their lives, focusing on attributes of age, gender, and cultural context of the child. Parts 3 and 4 utilize the lenses of children's rights principles and attributes to examine the potential for child-sensitive and child-just processes and outcomes of reparation. Ultimately, this paper seeks to fill a gap in literature for approaching reparations for child victims of armed conflict rooted in their experience of war and the impact of harms on their lives.